تطبيقات قواعد الشكل في التعليم المعماري - رمزي الشيخ; نسيبة سعيد; منال سلهب (Tishreen University, 2019)
The research proceeds by introducing the concept of the Shape grammar, its components and its applications in both: analytical educational approach and Synthetically approach, with a historical narrative of the sequence of the application of Shape grammar according to three levels: the definition of the original design, the analytical level, and then the analysis of the original design. In order to achieve the objective of research in determining the mechanism of the development of architectural education using Shape grammar, and its role in the advancement of ways to teach students from the first phase students, And then test the ability of graduate students to analyze the architectural works of historical and contemporary, and the possibility of developing new architectural languages derived from the original design reflects the student's ability to analysis and creativity, As well as to benefit from the research of graduate students in developing the mechanism of the work of Shape grammar and the creation of new ways in architectural education around the world. In order to determine the pros and cons of the application of the shape grammar in the field of education, and to develop proposals to provide the educational process in the Syrian universities at various stages. يسير البحث من خلال التعريف بمفهوم قواعد الشكل, ومكوناته, وتطبيقاته بشقيها التحليلي التعليمي والتصميمي, وذلك بسرد تاريخي لتسلسل تطبيقات قواعد الشكل وفق ثلاث مستويات وهي: التعريف بالتصميم الأصلي, المستوى التحليلي, ومن ثم تحليل التصميم الأصلي. من أجل تحقيق هدف البحث في تحديد آلية تطوير التعليم المعماري باستخدام قواعد الشكل, ودوره الكبير في الارتقاء بطرق تعليم الطلاب ابتداء من طلاب المرحلة الأولى, ثم اختبار قدرة طلاب التخرج على تحليل الأعمال المعمارية التاريخية والمعاصرة, وإمكانية وضع لغات معمارية جديدة مستمدة من التصميم الأصلي تعكس قدرة الطالب على التحليل والإبداع, وأيضا الاستفادة من أبحاث طلاب الدراسات العليا في تطوير آلية عمل قواعد الشكل وابتكار طرق جديدة في التعليم المعماري حول العالم. ليصار إلى تحديد إيجابيات وسلبيات تطبيقات قواعد الشكل في المجال التعليمي, ووضع اقتراحات ترفد العملية التعليمية المعمارية في الجامعات السورية في مراحلها المختلفة.